2017
DOI: 10.1063/1.4973366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface strain on the spin dynamics of deposited Co nanowires

Abstract: Tailoring the magnetic properties at atomic-scale is essential in the engineering of modern spintronics devices. One of the main concerns in the novel nanostructured materials design is the decrease of the paid energy in the way of functioning, but allowing to switch between different magnetic states with a relative low-cost energy at the same time. Magnetic anisotropy (MA) energy defines the stability of a spin in the preferred direction and is a fundamental variable in magnetization switching processes. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The nature of such couplings and their contribution to the magnetization direction have been discussed everywhere. See refs , , and , for instance.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of such couplings and their contribution to the magnetization direction have been discussed everywhere. See refs , , and , for instance.…”
Section: Resultsmentioning
confidence: 99%
“…These NWs show enhanced magnetism, as compared to their bulk (3D) state, and quantized conductance. They are predicted to be technologically useful for spintronics-based devices. , Various studies have been carried out on 1D monatomic chains , including transition elements of 3d series, ,,− 4d series, , 5d series, ,,, and alkali metals. It was found that Pt nanowires exhibit Hund’s rule magnetism, and the magnetic moment increases upon stretching; however, in the bulk state Pt does not show magnetism . Delin et al explored the spin dynamics of atomically thin platinum wires based on first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%